Cost-effectiveness of a rapid point-of-care test for diagnosing patients with suspected bloodstream infection in Ireland. (2022) - Vankelegom, Mathilde; Burke, David; Mohammed, Amr Mohammed Farghaly; McEvoy, Natalie L.; Curley, Gerard F.; Turner, Katy; Pinsent, Amy; Adams, Elisabeth J.
Abstract: A rapid point-of-care (PoC) test as an adjunct to blood culture to aid the diagnosis of sepsis patients with bloodstream infections may decrease the use of broad-spectrum antibiotics and reduce rates of inappropriate antimicrobial therapy (IAAT) use. Through a decision tree model, taking the perspective of the Irish healthcare provider, the cost-effectiveness of such an intervention was evaluated against the current standard of care (SoC) in hospitalized adults in Ireland. The base-case scenario showed that using a rapid PoC test was cost-saving and life-saving, with €8188 saved per death averted. The results were sensitive to the length of hospital stay for patients with true-positive and true-negative results and to the length of stay (LOS) in the intensive care unit. The threshold analysis showed that even at lower sensitivities, the rapid PoC test could be cost-effective due to the substantial impact of starting earlier targeted and appropriate treatment in patients with bloodstream infection (BSI) and sepsis.